Consumer alternative dispute resolution in emerging economies - Sahin-Sengül, Eda; Kaya, Serkan (Law teacher) (Routledge, 2025)
"This book provides a comprehensive guide to consumer Alternative Dispute Resolution (ADRs) and the unconventional challenges they pose for emerging economies, aiming to advance their growth within developing nations. Written in response to the increasing number of transactions between consumers and traders in the digital age, and the accompanying rise in consumer disputes, the book details ADR systems which have come to the fore to settle complaints. Covering ADR techniques including arbitration, mediation, and ombudsman services, it provides a guide to efficient dispute resolution and its application to emerging economies worldwide. The book also examines the role of technology in shaping ADR processes, given the prevalence of digital transactions in consumer markets. Thoughtfully explaining the challenges faced in implementing these systems, it suggests how governments and businesses can encourage the use of ADR, alongside providing practical case studies detailing past integrations into emerging economies. Practical, thorough and internationally focused, this book will be of interest to researchers in the field of dispute resolution, consumer law and technology"--